2001
DOI: 10.1177/088626001016008004
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal, Experiential, and Situational Predictors of Sexual Assault Perpetration

Abstract: Past research demonstrates that sexual assault perpetration is caused by multiple factors including attitudes, early experiences, and situational factors. In this study, 343 college men described either a sexual assault they had committed or their worst date. Discriminant function analysis indicated that attitudes about gender roles and alcohol, number of consensual sex partners, how well the man knew the woman, how isolated the setting was, alcohol consumption during the event, the man's misperception of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
281
2
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 245 publications
(308 citation statements)
references
References 36 publications
18
281
2
7
Order By: Relevance
“…First, heavy drinkers are likely to drink heavily in many types of situations, especially at parties and bars which are the types of situations in which sexual assault frequently occurs. Abbey et al (2001) found that college men who had perpetrated sexual assault tended to consume more alcohol in sexual situations than did college men who had not committed sexual assault. Second, heavy drinkers may simply use intoxication as an excuse for engaging in sexual assault (Scully, 1991).…”
Section: Sexual Experiences-menmentioning
confidence: 92%
See 3 more Smart Citations
“…First, heavy drinkers are likely to drink heavily in many types of situations, especially at parties and bars which are the types of situations in which sexual assault frequently occurs. Abbey et al (2001) found that college men who had perpetrated sexual assault tended to consume more alcohol in sexual situations than did college men who had not committed sexual assault. Second, heavy drinkers may simply use intoxication as an excuse for engaging in sexual assault (Scully, 1991).…”
Section: Sexual Experiences-menmentioning
confidence: 92%
“…College students have lower rates of agreement, although forcing sex is perceived as most justifiable in circumstances similar to those endorsed by high school students (Cook, 1995). College student perpetrators of sexual assault believe that using verbal pressure to obtain sex is more acceptable than do nonperpetrators (Abbey et al, 2001). As noted below, these attitudes about forced sex may be activated in drinking situations.…”
Section: Perpetrators' Attitudes About Women and Sexual Relationshipsmentioning
confidence: 96%
See 2 more Smart Citations
“…Numerous researchers have replicated these basic findings. Depending on the university and exactly how questions were phrased, self-reported rates of sexual assault perpetration have been as high as 61% and rates of attempted or completed rape have been as high as 15% [Abbey et al, 1998[Abbey et al, , 2001Craig et al, 1989;Mills and Granoff, 1992;Muehlenhard and Linton, 1987;Rapaport and Burkhart, 1984;Wheeler et al, 2002].…”
Section: Self-reported Rates Of Sexual Assault Perpetration In Collegmentioning
confidence: 99%